Pedicled gastric seromuscular patch for one-stage closure of a bronchopleural fistula: a case report - Jun Suzuki; Hiroyuki Oizumi; Hirohisa Kato; Akira Hamada; Hikaru Watarai; Kenta Nakahashi; Takayuki Sasage; Mitsuaki Sadahiro (Surgical Case Reports)
Abstract Background One-stage closure and fenestration are the available surgical options for bronchopleural fistula (BPF). One-stage closure may be applicable in cases with favorable infection control. Closing the bronchopleural stump is difficult due to thick adhesion caused by inflammation and a high risk of pulmonary artery injury. We report the successful closure of a BPF using a gastric seromuscular patch with an omental pedicle flap. Case presentation A 73-year-old man underwent right lower lobectomy with ND2a-2 lymph node dissection for lung adenocarcinoma. He was admitted to a local hospital for pneumonia. Three days after admission, his thoracic cavity was drained and a BPF was suspected. During the primary operation, the latissimus dorsi muscle and anterior serratus muscle were dissected via posterolateral incision, and we decided to close the fistula using the gastric seromuscular layer and omental pedicle flap. The patient was discharged 20 days after surgery. After 2 years, he has not had cancer recurrence and currently leads an active life. Conclusions This method provided immediate airtight closure and luminal opening of the middle bronchus in our patient with a large BPF and appeared superior to using the omentum alone. This procedure is useful for one-stage closure and does not require fenestration in cases with favorable infection control.